Airport planning: approaches to determining the planning horizon - Kazda, Antonín; Novák Sedláčková, Alena; Bračić, Matija (Transport, 2023)
Airport planning is a challenging task that requires knowledge of many standards and recommended practices, bylaws and procedures. Besides, it is possible that politicians would try to intervene in the planning process, which always exceeds the election period of one government. Therefore, the article provides in-depth theoretical analysis of the problem and summarizes the results of research that focused on comparing the approach to the airport planning issues in the Slovakia and Croatia. The primary goal was to develop a methodology for determining the airport planning horizon, to assess the significance of individual planning phases and to evaluate results. The research was carried out using a combination of several methods. The main challenge was to determine the length of the planning horizon. In 2 panels, 32 experts from Slovakia and Croatia were interviewed and 224 different responses were received and processed by the fuzzy Delphi method. The advantage of this approach relies on combination of well – developed theory and practical solutions in cooperation with experts from the industry. Despite the different legal frameworks and similar standards for airport planning in both countries, the results of the research proved that the values of the optimal planning horizons are comparable. As a result, the methodology can therefore be used in other countries with similar conditions. However, planning procedures and practices depend on the specifics of states or even regions. Eventually, the experience from the research provides relevant and robust material to support teaching. Besides, it is transferable to other fields of transport infrastructure planning. Additionally, the research results were provided to the state planning authorities.